Design of "Neuropsychological and Mental Health Outcomes of Operation Iraqi Freedom: A Longitudinal Cohort Study". (1st March 2013) - Aslan, Mihaela; Concato, John; Peduzzi, Peter N.; Proctor, Susan P.; Schnurr, Paula P.; Marx, Brian P.; McFall, Miles; Gleason, Theresa; Huang, Grant D.; Vasterling, Jennifer J.
Abstract : Objective: This study aimed to describe methodological challenges encountered in designing a follow-up assessment of US Army Soldiers who served in Operation Iraqi Freedom. Study Design and Setting: The Neurocognition Deployment Health Study (NDHS) enrolled 1595 soldiers at 2 military installations, starting in 2003. Prior work compared predeployment and postdeployment assessments among Iraq-deployed and nondeployed soldiers. The current phase, as VA Cooperative Studies Program #566, is collecting follow-up data on participants who were deployed to Iraq or Afghanistan. Specific aims include evaluating the prevalence and course of posttraumatic stress disorder (PTSD), the persistence of previously observed neuropsychological changes, and the relationship of these changes—and traumatic brain injury—to subsequent PTSD. The target sample size is 817 participants, with 200 participants also receiving performance-based neuropsychological assessments. Results: We describe 6 methodological challenges and their implications for longitudinal research among a "closed, " young, mobile study population: transitioning from cluster-based (battalion) sampling to individual-level sampling; overcoming practical barriers (such as location searches); selecting exposure and outcome measures that combine previously collected and current study data; accounting for loss of an exposed (deployed) versus (nonexposed) nondeployed comparison; determining timing of assessments; and developing a complex statistical analysis plan. Enrollment is ongoing. Conclusions: The study provides unique insights regarding elements of study design and analysis that are relevant to longitudinal research. In particular, the dynamic "real-life" context of military deployment provides a basis for applying observational methodology to characterize mental health disorders associated with exposure to war-zone deployment and other contexts associated with exposure to extreme stress.